বাংলাদেশে মাদকাসক্তি বৃদ্ধির গতি-প্রকৃতি: ইসলামের দৃষ্টিতে উত্তরণের উপায় অন্বেষণ | The Rise of Drug Addiction in Bangladesh: Searching of Ways to Minimize this Problem in the Context of Islam (ইসলামী আইন ও বিচার | Islami Ain O Bichar, 2023)
Although once drugs were once used for medicinal use for enjoyment and generating happy feelings, or as the erroneous recreation method to create tranquility, in the passage of time, it has emerged as a serious social problem and threat to mankind. This is why Islam, the safeguard for humanity, complete with codified laws, has announced the usage of drugs as ‘haram’ (forbidden), along with the rules for punishment to protect human conscience for the purpose of establishing a healthy and vigorous body, and an intellectual and creative society. Though various contemporary laws have been promulgated and are in effect, it has not been in control as per expectation. To control this crime, an integrated and harmonized system of both conventional and Islamic law is needed. This article has aimed to define Islamic perspective of drugs, and employs descriptive and explanatory methods in conducting this research. The article has showed that so called modernism and fashion, the effects of fundamentalism, lack of true religious practices, and laxity in religious observations are pushing the young generation to drug addiction at an alarming rate. In fact, in the present context, if the gradual increase in the number of drug addicts continues, soon our dear Bangladesh will turn into a backward and paralyzed nation.সারসংক্ষেপ: মাদকদ্রব্য এক সময় চিকিৎসা ক্ষেত্রে কিংবা আনন্দ-উল্লাস ও খোশ মেজাজে থাকার অনুভূতি এবং প্রশান্তি সৃষ্টির ভ্রান্ত বিনোদন হিসেবে ব্যবহৃত হলেও কালের চক্রে তা এখন মানব জাতির জন্য হুমকি এবং ভয়াবহ সামাজিক সমস্যা হিসেবে আত্মপ্রকাশ করেছে। এ কারণেই মানবতার রক্ষাকবচ ইসলাম মানুষের বিবেধ-বুদ্ধিকে হিফাজতের জন্য সুস্থ ও সবল দেহ, মেধা ও মননশীল সমাজ বিনির্মাণের উদ্দেশ্যে মাদকদ্রব্যের ব্যবহার চিরতরে হারাম ঘোষণা করে শাস্তির বিধান রেখে বিধিবদ্ধ আইন প্রণয়ন করেছে। প্রচলিত নানা আইন দিয়ে কাক্সিক্ষত মাত্রায় এর প্রতিরোধ সম্ভব হচ্ছে না। এ অপরাধের লাগাম টেনে ধরার জন্য প্রচলিত ও ইসলামী আইনের আলোকে একটি সমন্বিত ব্যবস্থার প্রয়োজন। মাদকের প্রতি ইসলামের দৃষ্টিভঙ্গি বর্ণনার উদ্দেশ্যেই আলোচ্য প্রবন্ধটি প্রণীত হয়েছে। এ গবেষণায় বর্ণনা, বিশ্লেষণ ও তুলনামূলক পদ্ধতি অনুসরণ করা হয়েছে। প্রবন্ধ থেকে প্রতীয়মান হয়েছে, তথাকথিত আধুনিকতা ও ফ্যাশনের নামে কিংবা ধর্মান্ধতার কুফলের দোহাই দিয়ে প্রকৃত ধর্মচর্চা তথা ধর্মীয় অনুশাসন পালনের ক্ষেত্রে শিথিলতা এবং অনেক ক্ষেত্রে অবচেতন হওয়ার কারণেই আমাদের তরুণ প্রজন্ম আশঙ্কাজনক হারে মাদকাসক্তির প্রতি ঝুঁকে পড়ছে। দেশে মাদকাসক্তি ক্রমবিস্তারের বিদ্যমান পরিস্থিতি অব্যাহত থাকলে অচিরেই আমরা একটি পশ্চাৎপদ ও পঙ্গু জাতিতে পরিণত হওয়ার আশঙ্কা রয়েছে।